PSYCHOLOGICAL ADAPTATION PROBLEMS OF FRESHMEN TO THE LEARNING ENVIRONMENT IN HIGHER EDUCATION ESTABLISHMENT - Бондар, Л. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
In the article the questions of students’ adaptation of the first course to teaching in Institutes and Universities are examined .Adaptation depends on the skills of independent work and of educational-cognitive interest